Georgia O'Keeffe - Beal, Jeff 1963- (Sony Pictures Home Entertainment, 2010)
Follows the life of American artist Georgia O'Keeffe and her tumultuous relationship with her husband, photographer Alfred Stieglitz. As their relationship suffers, Alfred takes a younger lover. Georgia's search for solace moves her west, where she finds new inspiration for her paintings, and ultimately her own voice, in the New Mexico landscape